MYSTICAL - PHILOSOPHICAL VIEWS OF KHOJA AHMAD YASSAVI (Scientific journal of the Fergana State University, 2024)
In this article, the mystical-philosophical views of the poet and thinker, Sufi sage Khoja Ahmed Yassavi are analyzed from the perspective of the foundations of the history of philosophy.